2002
DOI: 10.1089/10430340252898993
|View full text |Cite
|
Sign up to set email alerts
|

Use of Spontaneous Epstein-Barr Virus-Lymphoblastoid Cell Lines Genetically Modified to Express Tumor Antigen as Cancer Vaccines: Mutated p21rasOncogene in Pancreatic Carcinoma as a Model

Abstract: Spontaneous Epstein-Barr virus (EBV)-transformed lymphoblastoid cell lines (SP-LCLs) can be easily obtained from latently EBV-infected cancer patients and used as a source of antigen-presenting cells (APCs) for immunotherapy. Using point-mutated (codon 12) p21(ras) (muRas) as a model tumor antigen, we evaluated the practicability of using genetically modified SP-LCLs as cancer vaccines for patients with pancreatic cancer expressing mutated Ras (muRas). The repeated stimulation of peripheral blood mononuclear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Several phase I studies using various vaccine strategies similar to those previously evaluated in malignant melanomas 40 -42 have suggested the safety of this approach in pancreatic cancer patients. [43][44][45] While all patients with a tumor that expresses a given CT antigen would be candidates for vaccine strategies using whole antigenic proteins, the percentage of patients eligible for peptidespecific vaccination would be much lower since it requires antigenic peptides with binding motifs restricted to specific MHC alleles. Therefore, additional antigenic CT genes must be identified for human pancreatic carcinoma, especially if the goal is to develop multivalent vaccines for a majority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several phase I studies using various vaccine strategies similar to those previously evaluated in malignant melanomas 40 -42 have suggested the safety of this approach in pancreatic cancer patients. [43][44][45] While all patients with a tumor that expresses a given CT antigen would be candidates for vaccine strategies using whole antigenic proteins, the percentage of patients eligible for peptidespecific vaccination would be much lower since it requires antigenic peptides with binding motifs restricted to specific MHC alleles. Therefore, additional antigenic CT genes must be identified for human pancreatic carcinoma, especially if the goal is to develop multivalent vaccines for a majority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity assay. As described earlier (28), T-cell cultures were tested for their specific cytotoxicity in a DNA fragmentation assay (30) ) were then added to varying numbers of effector cells in V-bottomed microwells. After incubation for 4 hours at 37jC, plates were centrifugated.…”
Section: Methodsmentioning
confidence: 99%
“…In two small trials, activated B lymphocytes have been safely piloted as part of vaccines. 45,46 Activated autologous lymphoblastoid cell lines (LCL) were transfected ex vivo with mutated p21ras (muRas) as a model tumor antigen and used as a vaccine in pancreatic carcinoma. LCL transfected with muRas were capable of inducing antigen-specific CTL responses both in vitro and in one pancreatic cancer patient, demonstrated by specific lysis of target cells loaded with immunogenic peptides derived from muRas and peptide-specific IFN-gamma secretion.…”
Section: © L a N D E S B I O S C I E N C E 2 0 0 3 N O T F O R D I mentioning
confidence: 99%
“…LCL transfected with muRas were capable of inducing antigen-specific CTL responses both in vitro and in one pancreatic cancer patient, demonstrated by specific lysis of target cells loaded with immunogenic peptides derived from muRas and peptide-specific IFN-gamma secretion. 46 In addition to Epstein-Barr Virus-transformed LCL cells, CD40-activated nontransformed B cells (CD40-B) have also been studied. Schultze et al first reported that peptide-loaded CD40-B are as effective as DC in the induction of autologous antigen-specific T cell responses against both viral and tumor associated antigens in vitro.…”
Section: © L a N D E S B I O S C I E N C E 2 0 0 3 N O T F O R D I mentioning
confidence: 99%